Diverse in- and output polarities and high complexity of local synaptic and non-synaptic signaling within a chemically defined class of peptidergic Drosophila neurons - Karsai, Gergely; Pollák, Edit; Wacker, Matthias; Vömel, Matthias; Selcho, Mareike; Berta, Gergely; Nachman, Ronald J.; Isaac, R E.; Molnár, László; Wegener, Christian (Frontiers in Neural Circuits, 2013)
Peptidergic neurons are not easily integrated into current connectomics concepts, since their peptide messages can be distributed via non-synaptic paracrine signalling or volume transmission. Moreover, the polarity of peptidergic interneurons in terms of in- and output sites can be hard to predict and is very little explored. We describe in detail the morphology and the subcellular distribution of fluorescent vesicle/dendrite markers in CCAP neurons (NCCAP), a well defined set of peptidergic neurons in the Drosophila larva. NCCAP can be divided into five morphologically distinct subsets. In contrast to other subsets, serial homologous interneurons in the ventral ganglion show a mixed localisation of in- and output markers along ventral neurites that defy a classification as dendritic or axonal compartments. Ultrastructurally, these neurites contain both pre- and postsynaptic sites preferably at varicosities. A significant portion of the synaptic events are due to reciprocal synapses. Peptides are mostly non-synaptically or parasynaptically released, and dense-core vesicles and synaptic vesicle pools are typically well separated. The responsiveness of the NCCAP to ecdysis-triggering hormone may be at least partly dependent on a tonic synaptic inhibition, and is independent of ecdysteroids. Our results reveal a remarkable variety and complexity of local synaptic circuitry within a chemically defined set of peptidergic neurons. Synaptic transmitter signalling as well as peptidergic paracrine signalling and volume transmission from varicosities can be main signalling modes of peptidergic interneurons depending on the subcellular region. The possibility of region-specific variable signalling modes should be taken into account in connectomic studies that aim to dissect the circuitry underlying insect behaviour and physiology, in which peptidergic neurons act as important regulators.